Supplementation With Spirulina Reduces Infarct Size and Ameliorates Cardiac Function in a Pig Model of STEMI - Gemma Vilahur; Gemma Vilahur; Pablo Sutelman; Soumaya Ben-Aicha; Guiomar Mendieta; Guiomar Mendieta; Monika Radiké; Leonie Schoch; Laura Casaní; Laura Casaní; María Borrell-Pagés; Teresa Padro; et al. (Frontiers Media S.A., 2022)
Background and Aims: Myocardial infarction (MI) is the clinical manifestation of atherosclerotic coronary artery disease. Spirulina is an algae known to ameliorate cardiometabolic disorders and with proven anti-inflammatory and anti-oxidant effects. We investigated, in a highly translatable animal model, whether oral supplementation with spirulina protects against the deleterious effects triggered by ST-elevation MI (STEMI).Methods: Pigs were fed a regular diet supplemented with spirulina (1 g/animal/bid) or placebo-control for 10 days. Thereafter, animals were subjected to 1.5 h percutaneous balloon-induced coronary occlusion (STEMI) followed by 2.5 h reperfusion and then sacrificed. We assessed infarct size and cardiac function. Blood samples and infarcted and remote myocardial tissue were obtained.Results: Spirulina supplementation reduced infarct size by 64%, increased myocardial salvage by 18%, and improved cardiac function by 30% vs. controls (p < 0.05). These benefits were associated with attenuation in DNA-oxidative damage and apoptotic markers and increased iNOS in the infarcted myocardium, higher AMPK activation in the remote myocardium, and lower myocardial MCP-1 expression. Systemically, spirulina attenuated Cox-2 expression in STEMI-activated peripheral blood mononuclear cells and enhanced TNF-α release acutely post-STEMI. Additionally, spirulina decreased weight gain progression over time (p < 0.05) without changes in lipids, glucose, liver or kidney parameters.Conclusion: A 10-day supplementation with spirulina exerts cardioprotection in a preclinical setting of STEMI by limiting cardiac damage and improving ventricular contractility through anti-oxidative, anti-inflammatory, and anti-apoptotic mechanisms.